Ecosystem Restoration is Now a Global Priority: Time to Roll up our Sleeves. Issue 3 (18th February 2013) - Aronson, James; Alexander, Sasha
Abstract Ecosystem restoration is now globally recognized as a key component in conservation programs and essential to the quest for the long‐term sustainability of our human‐dominated planet. Restoration scientists and practitioners are now on the frontline and will be increasingly called upon to get involved in large scale programs addressing immediate environmental crises and challenges. Here, we summarize the advances in mainstreaming ecological restoration in global environmental policy deliberations during the last year, culminating in the recent meeting of the United Nations Convention on Biological Diversity. We also provide key references for those seeking more information, and set out an agenda as to how the restoration community could respond to and act upon these recent developments. However, we underline the need for caution and prudence; we must not promise more than we can deliver. Thirty years after the emergence of ecological restoration as a scientific discipline and practice, there remain many obstacles and misconceptions about what can be achieved at large scales. Yet, clearly the old adage applies here: nothing ventured, nothing gained.